In vitro antiplasmodial activities of the fractions of Hyrtios reticulatus sponge extract - Mahfur Mahfur,, Indah Purwantini, Subagus Wahyuono, Erna Prawita Setyowati (Journal of Applied Pharmaceutical Science, 2022)
The discovery of new compounds sourced from nature, which are active against malaria, is very important. Sponge Hyrtios reticulatus from Bali, Indonesia, is one of the examples that can be investigated. The sponge samples were extracted using ethanol, followed by trituration fractionation and vacuum liquid chromatography to get the samples. The nine samples obtained, their main extracts, chloroform fraction, residue, and SF 1–9 were tested for activities against Plasmodium falciparum variants 3D7 and FCR3. The results showed that all samples had a moderate antiplasmodial activity, where the most active sample was SF 3 with an IC50 of 12.98 ± 1.88 µg/ml on 3D7 and 19.81 ± 0.75 µg/ml on FCR3. This study discovered that H. reticulatus sponges had antiplasmodial activities and could be further used as a guide to finding a new antiplasmodial compound.
Keywords: Hyrtios reticulatus, antiplasmodial, malaria, 3D7, FCR3